2010
DOI: 10.1007/s12540-010-0013-z
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of slurry erosion resistance of martensite/ferrite duplex stainless steel by hot rolling

Abstract: Test samples of martensite/ferrite duplex stainless steels (M/Fss) were prepared using thermal-mechanical processes and their slurry erosion behaviors were systematically studied. Test results show that hot rolling is an attractive process for improving erosion resistance. This improvement is more evident at higher impinging angles and larger reduction ratios. The thermal-mechanical-treated samples exhibit higher slurry erosion resistance for all impinging angles compared to that obtained by conventional quenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Due to work hardening and martensite formation with grain refinement, hot rolled M/Fss exhibited the improved SE resistance, while compared to conventional quenched steels, especially with excellent performance at higher values of impingement angles and reduction ratios. 70 Perspective on best technologies for rectifying the tribo-se performance Tribo-performance of materials chiefly and mostly depends upon their mechanical properties, consequently the styles of erosion; ductile, brittle or mixed modes of erosion. Many researches (previous sections) related to technologies for enhancing the resistance to SE by improving the microstructures and properties have been focused and performed.…”
Section: Heat Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to work hardening and martensite formation with grain refinement, hot rolled M/Fss exhibited the improved SE resistance, while compared to conventional quenched steels, especially with excellent performance at higher values of impingement angles and reduction ratios. 70 Perspective on best technologies for rectifying the tribo-se performance Tribo-performance of materials chiefly and mostly depends upon their mechanical properties, consequently the styles of erosion; ductile, brittle or mixed modes of erosion. Many researches (previous sections) related to technologies for enhancing the resistance to SE by improving the microstructures and properties have been focused and performed.…”
Section: Heat Treatmentmentioning
confidence: 99%
“…23 mode of erosion, maximum erosion takes place at the angles somewhere in between low and high angles of impact (refer Figure 3). Some literary works 45,70 depicted two types of mechanism for material removal in SE. One is deformation wear notable at high impact angles and other as cutting wear prominently occurring at low angles of impingement (refer Figure 4 (a and b)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slurry erosion resistance of the 13/4 MSS can be economically improved by the application of TMP because this steel gains its useful hardness and erosion resistance from austenite to martensite transformation [13]. For example, Wen [14] concluded that hot rolling is an attractive process for improving the erosion resistance of martensite/ferrite duplex stainless steels. Beneficial effect of warm multidirectional forging on the refinement in microstructure, improvement of mechanical properties and slurry erosion resistance in high-strength-low-alloy (HSLA) steel is reported [15].…”
Section: Introductionmentioning
confidence: 99%
“…The sticking amount is also varied with the kind of ferritic stainless steels because their alloying elements affect the high-temperature hardness and oxidation. [12][13][14] Furthermore, the addition or modification of alloying elements is required to replace austenitic stainless steels, which can cause the serious sticking and consequent reduction in productivity of ferritic stainless steels. Therefore, the effects of alloying elements on sticking are essentially needed to prevent or minimize sticking and the development of advanced ferritic stainless steels with improved corrosion resistance, but only limited information is available.…”
Section: Introductionmentioning
confidence: 99%